More caseworkers shorten unemployment durations and save costs - René Böheim; Rainer Eppel; Helmut Mahringer (Johannes Kepler University of Linz, Department of Economics, 2022)
In a randomized controlled trial in Austria, lower caseloads in public employment offices led to more meetings of the unemployed with their caseworkers, more job offers, more program assignments, and more sanctions for noncompliance with job search requirements. More intensive counseling led to shorter unemployment episodes due to faster job entry, but also to more exits from the labor force in the two years following treatment. We find effects for different subgroups of unemployed. We find no effects on wages. A cost-benefit analysis suggests that lower caseloads not only shorten the duration of unemployment but are also cost-effective.
Keywords: J64; J68; 330; Active labor market policy; Public Employment Services; caseworkers; counseling; job placement; field experiment